2007
DOI: 10.1093/ps/86.2.318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Levels of Conjugated Linoleic Acid Supplementation on Fatty Acid Content and Carcass Composition of Broilers

Abstract: The effects of dietary conjugated linoleic acid (CLA) supplementation on growth performance, carcass quality, free fatty acid composition, and accumulation of CLA were investigated in broilers. Four hundred eighty 3-wk-old broilers were assigned to 4 dietary treatments (0, 0.5, 1.0, and 1.5% CLA) with 6 replicates of 20 chickens. Feed consumption and BW were recorded at every 5-d period. On d 42, carcass compositions were determined from 30 birds per treatment. There were no significant differences in average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 33 publications
6
41
1
1
Order By: Relevance
“…Similar findings were reported by Schiavone et al (2004), who stated that the mean values for moisture, protein and lipid contents of breast meat of Muscovy duck were not significantly influenced by dietary FO. Suksombat et al (2007) also indicated that moisture, crude protein and fat contents of carcass were not affected by the consumption of conjugated linoleic acid. As shown in Table 3, no significant differences could be observed among dietary treatments in meat tenderness and pH, however, a dietary mixture of 1% FO + 1% LO increased the water-holding capacity of meat.…”
Section: Discussionmentioning
confidence: 88%
“…Similar findings were reported by Schiavone et al (2004), who stated that the mean values for moisture, protein and lipid contents of breast meat of Muscovy duck were not significantly influenced by dietary FO. Suksombat et al (2007) also indicated that moisture, crude protein and fat contents of carcass were not affected by the consumption of conjugated linoleic acid. As shown in Table 3, no significant differences could be observed among dietary treatments in meat tenderness and pH, however, a dietary mixture of 1% FO + 1% LO increased the water-holding capacity of meat.…”
Section: Discussionmentioning
confidence: 88%
“…This result is basically in line with Du and Ahn (2002) who reported that CLA accumulated in the breast and leg muscles lipid and accounted for approximately 10 g/100 g fatty acids present in birds fed 15 g CLA/kg diet. Moreover, Suksombat et al (2007) reported that feeding incremental levels of dietary CLA (0.0-1.5%) resulted in linear increases of CLA isomers concentrations in muscle tissue lipids of Arbor Acres broilers. It has already been demonstrated that CLA is readily incorporated into the egg of laying hen (Chamruspollert and Sell 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In the CLA diet, 1.5% soybean oil was replaced by 1.5% CLA to keep both the CLA-supplemented diet and the control diet isoenergetic. The 1.5% CLA inclusion level was chosen as previous findings showed that with higher inclusion levels the CLA deposition efficiency decreased (Du and Ahn 2002;Suksombat et al 2007;Narciso-Gaytan et al 2011). The accumulation of CLA in meat increases linearly with the CLA level (0~1.5%) increasing in the diet.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Jiang et al (2014) observed no significant effects on growth performance with 1% CLA supplementation. However, literature is inconsistent because several studies found that dietary supplementation with CLA at levels greater than 10 g/kg decreased the growth rate of broilers (Szymczyk et al 2001;Suksombat et al 2007). Moraes et al (2016) found that CLA exhibited negative effects on performance that could be observed not only at 2% CLA inclusion, but also at 1% CLA inclusion.…”
Section: Effects Of Dietary Cla On On the Growth Performance Of Broilmentioning
confidence: 99%